Logos, Inspiration, and Self-Motion in Plato’s Phaedrus - Bickford, Susan (Plato Journal, 2024)
Plato is often seen as the quintessential champion of reason, but many of his dialogues dramatize the insufficiency of certain conceptions of reason for ethical and political life. In this article, I trace out the multiple forms and purposes of reason and inspiration in Plato’s Phaedrus, and show that each can be discerning or misleading. No method of reason or experience of inspiration can automatically provide secure moral knowledge. Instead of certainty, the Phaedrus recommends a kind of self-motion that requires an ongoing choice of self via an ongoing practice of logos with others. In this practice, reason intertwines with other forces to ask and answer the questions generated by the multiple values of the soul.